(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
To figure out the underground structures, the tectonic framework, and the minerals in the area., the transition zone of the Mambila Plateau and surroundings in northeastern Nigeria has been explored utilizing aeromagnetic, pseudo gravity, and landsat-8 remotely sensed. Several depth estimation and filtering methods, such as the first vertical derivative, total horizontal derivative, and total gradient, were used on the magnetic data (analytical signal), upward continuation, and pseudo gravity transform. Using landsat-8 imagery data, aeromagnetic, and pseudo gravity transforms, it was possible to identify mineral zones with hydrothermal changes, shallow and deep intrusive masses, buried faults, lineaments, and lithological units. A thorough field mapping revealed and confirmed a few mineralization zones with great potential. The mining areas exhibit high structural density, which highlights the value of lineaments density maps in identifying probable mineralization zones and the structures that regulate mineralization. The principal tectonic trends are NE-SW, NNE-SSW along with less significant NNW, WNW, NS, and NE trends, is shown by statistical trend analysis of the lineaments collected from geological, filtered magnetic, and density maps. The corresponding magnetic structures were scanned upward continuing at depths ranging from the surface to 3000m. Power spectrum and source parameter imaging approaches have been used to determine the depth of a structure. The results reveal that the average computed depth ranges from 1.2 km to 1.7 km, whereas the depth to volcanic intrusions ranges from 0.345 km to 0.461 km